Voting under the threat of secession: Accommodation vs. repression - Vincent Anesi; Philippe De Donder (Center for Economic Studies and ifo Institute (CESifo), 2011)
We build a model of secession crises where voters may wish to accommodate the minority to prevent secession. We show the existence of a majority voting equilibrium with a government's type biased in favor of the minority. We propose a measure of secession risk and perform the comparative static analysis of the equilibrium policy location and of the secession risk with respect to the cultural distinctiveness of the two regions, the relative weight attached by voters to economic factors, the relative size of the minority region, the probability that a secession attempt is successful, and the intra-regional heterogeneity of preferences.
Keywords: D72; D74; 330; majority voting; secession risk; cultural distinctiveness; conflict; overlapping regional preferences; Separatismus; Risiko; Minderheitenpolitik; Wahlverhalten; Sozialgeographie; Theorie